Entertainment Design in Mixed Martial Arts: Does Cage Size Matter? - Paul Gift (Journal of Applied Sports Management, 2019)
This paper investigates the effect of a change in cage size on fighter performance outcomes in Zuffa-owned mixed martial arts (MMA) promotions. Variation in cage size is observed through different events over time in the Ultimate Fighting Championship (UFC) and World Extreme Cagefighting (WEC). Results suggest that smaller cages lead to more fight finishes (knockouts and submissions) and higher rates of distance knockdowns and choke attempts, all exciting outcomes for viewers. But they also lead to a higher proportion of time with fighters pressed against the cage, a position some viewers may dislike. Since MMA promoters com-pete with other forms of entertainment, findings have strategic implications for promoter cage-size decisions. Subscribe to JASM
Keywords: Cage size; entertainment; fighter performance; mixed martial arts; Ultimate Fighting Championship (UFC); World Extreme Cagefighting (WEC)